Impact of Domestication on the Endophytic Fungal Diversity Associated With Wild Zingiberaceae at Mount Halimun Salak National Park - Ivan Permana Putra; Gayuh Rahayu; Iman Hidayat (Bogor Agricultural University, Indonesia, 2015)
Mount Halimun Salak National Park is one of the tropical forest remnants in Java island. The national park has been recognized with high diversity of wild Zingiberaceae. Of that Zingiberaceae, two species namely Alpinia malaccensis (AM) and Horstendia conica (HC), were domesticated as garden plants in the surrounding area of the forest for medicinal use. The impact of domestication on the fungal endophytes associated with these two species of Zingiberaceae is reported here. Fungal endophyte diversity in the wild and domesticated AM and HC was analyzed based on the culturable fungi. Identification of species level used morphological and molecular approaches of ITS rDNA sequence. This study determined 19 species of fungal endophytes, namely Arthrinium malaysianum, Aspergillus flavipes, As. sydowii, Chaetomium globosum, Cladosporium oxysporum, Cladosporium sp., Colletotrichum boninense-complex, Co. cliviae-complex, Co. gloeosporioides-complex, Diaporthe sp., D. anacardii, D. gardenia, Exophiala sp., E. lecanii-corni, Guignardia mangiferae, Ochroconis gallopava, Penicillium citrinum, Pyricularia costina, and unsporulated Sydowiellaceae. Among them, A. malaysianum, C. globosum, Co. cliviae-complex, D. gardenia, and unsporulated Sydowiellaceae were only found in domesticated plants, while some others were absent. Colletotrichum boninense-complex was commonly found in both wild and domesticated plants. Domestication activity affected the diversity of endophytic fungi of AM and HC.